Campus Madrasah Diniyah (CMD): Optimization of Islamic Education and Moral Education for Students - Abdul Wahhab (Proceedings of The ICECRS, 2020)
In contemporary Indonesia, one of the biggest phenomenon is the muslim scholars moral decadence that caused by a religious knowledge deficiency. The things that muslim educationalists can do are devising a new innovation in teaching and learning of Islamic studies and introducing a new idea to decline the number of moral decadence in muslim scholars. Therefore, the researcher come up with an idea related to the problem-solving of declining the number of moral decadence – Campus Madrasah Diniyah (CMD). Madrasah Diniyyah is the religious school which study about the Islamic studies. It becomes the new innovation of Madrasah Diniyyah in this contemporary country which provide the Islamic studies for the scholars. Then the library research and the descriptive qualitative methods are used by the researcher to analyze the phenomenon inside the moral decadence of Indonesian Muslim scholars. Also, to get the data analysis, the researcher analyze the previous researches and some books which related to the phenomenon.